EXPERIMENTAL INVESTIGATION ON COOLING EFFECT OF SPHERICAL DIMPLED PROFILE ALUMINUM BLOCK BY THE TAGUCHI METHOD - Ganesan, H. N.; Kasim, M.S.; Anand, J.S.; Abdullah, Z.; Zakaria, K.A.; Masripan, N.A.; Ab Maulod, H.E.; Nawi, M.A.M.; Ito, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Dimple profile plays a crucial role in enhancement of cooling process of various engineering application. This paper presents experimental investigation of convection heat transfer over spherical dimple on an aluminum block. In this study, an experimental investigation was carried out to observe the cooling effect under several conditions which are flow condition, dimple orientation, diameter of dimple, room temperature, air velocity, input of heat energy and condition of wind tunnel. A design of experiments technique was adopted in the form of orthogonal array L8 (23), Taguchi 2-Level approach. A total of 4 types dimpled surface are studied. The ANOVA results shows the room temperature is the major contributing factor towards rapid cooling process followed by wind tunnel condition, radius of dimple, air velocity, flow region and heat input. It was observed that the cooling time of 13 minutes can be achieved during laminar flow, 5 mm of dimple diameter, 60° angle of dimple orientation, 18 m/s of air velocity, 20 °C of room temperature.